2020
DOI: 10.1515/reveh-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate – properties, toxicity and human health effects: an updated review

Abstract: Interest in perchlorate as environmental pollutant has increased since 1997, when high concentrations have been found in the waters of the Colorado River, USA. Perchlorate is very persistent in nature and it is slowly degraded. Although harmful effects of large doses of perchlorate on thyroid function have been proven, the environmental effects are still unclear. The primary objective of the present review is to collect prevailing data of perchlorate exposure and to discuss its impact on human health. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 127 publications
(171 reference statements)
1
44
0
Order By: Relevance
“…It can be naturally introduced into water bodies from fertilizer run-offs and potash ores, unfortunately, perchlorates are highly stable and persistent in the environment and can cause a disruption in the functionality of the thyroid gland when ingested in humans at high concentrations. Perchlorates cause disruption by blocking the protein responsible for pumping iodine, hence inhibit the uptake of iodine into the body [52] [53] [54]. Magnetospirillum, another prevalent microbe discovered at both docking sites, belongs to the diverse group of Magnetotactic bacteria (MTB).…”
Section: Discussionmentioning
confidence: 99%
“…It can be naturally introduced into water bodies from fertilizer run-offs and potash ores, unfortunately, perchlorates are highly stable and persistent in the environment and can cause a disruption in the functionality of the thyroid gland when ingested in humans at high concentrations. Perchlorates cause disruption by blocking the protein responsible for pumping iodine, hence inhibit the uptake of iodine into the body [52] [53] [54]. Magnetospirillum, another prevalent microbe discovered at both docking sites, belongs to the diverse group of Magnetotactic bacteria (MTB).…”
Section: Discussionmentioning
confidence: 99%
“…People are exposed to perchlorates by transdermal contact, inhalation and ingestion. These compounds were classified as goitrogen due to their ability to inhibit the iodine uptake by thyroid cells disrupting the metabolism of thyroid hormones [ 111 , 112 ]. It is difficult to avoid perchlorate exposure, but its negative effects can be minimized by getting enough iodine in one’s diet or using iodized salt.…”
Section: The Most Common Edcsmentioning
confidence: 99%
“…The CONTAM Panel indicated newborns, infants and toddlers as the most vulnerable group to perchlorate acute toxicity [11]. Perchlorate can enter the human body via transdermal, inhalation and, most importantly, oral routes of exposure [7]. It was revealed that breast milk and powdered infant formulas (PIFs) are the most likely sources of perchlorate for newborns and infants [12].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal thyroid function caused by the perchlorate toxicity may lead to serious physical, as well as mental health issues [6]. A comprehensive review of the perchlorate properties, sources and toxicity to humans has been recently published elsewhere by the Authors [7].Regulatory status of perchlorate seems to be controversial and uncertain. In 1998, perchlorate were placed on the Contaminate Candidate List 1 (CCL1) published by the United States Environmental Protection Agency (USEPA).…”
mentioning
confidence: 99%
See 1 more Smart Citation